2020
DOI: 10.3390/nu12102966
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Effects of Dietary Supplementation of Lutein with High Bio-Accessibility on Macular Pigment Optical Density and Contrast Sensitivity: A Randomized Double-Blind Placebo-Controlled Parallel-Group Comparison Trial

Abstract: Improvements in macular pigment optical density (MPOD) and contrast sensitivity after administration of 12 mg lutein alone and the timing at which efficacy is observed remain unknown. Therefore, lutein (12 mg), a crystalline formulation, was used in this study, considering its bioaccessibility. This study aimed to determine the effects of lutein administration for 16 weeks on MPOD, contrast sensitivity, and glare sensitivity, and changes in serum lutein levels were determined. The study subjects comprised 59 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 27 publications
2
9
0
Order By: Relevance
“…Lutein from foods or supplem creases blood levels and macular pigment optical density (MPOD) in the retina i dependent manner (Figure 3) [81][82][83]. MPOD is related to static indicators of visual performance, such as glare and sensitivity, and dynamic measures of visual performance such as the critical flick threshold [84][85][86]. MPOD is also related to measures of cognitive function such fluency, memory, processing speed and accuracy [76].…”
Section: Luteinmentioning
confidence: 99%
See 1 more Smart Citation
“…Lutein from foods or supplem creases blood levels and macular pigment optical density (MPOD) in the retina i dependent manner (Figure 3) [81][82][83]. MPOD is related to static indicators of visual performance, such as glare and sensitivity, and dynamic measures of visual performance such as the critical flick threshold [84][85][86]. MPOD is also related to measures of cognitive function such fluency, memory, processing speed and accuracy [76].…”
Section: Luteinmentioning
confidence: 99%
“…The omega-3 (n-3) long-chain polyunsaturated fatty acids EPA (C20:5n-3) a MPOD is related to static indicators of visual performance, such as glare and contrast sensitivity, and dynamic measures of visual performance such as the critical flicker fusion threshold [84][85][86]. MPOD is also related to measures of cognitive function such as verbal fluency, memory, processing speed and accuracy [76].…”
Section: Eicosapentaenoic Acid (Epa) and Docosahexaenoic Acid (Epa)mentioning
confidence: 99%
“…Both lutein and zeaxanthin absorb blue light with a peak close to 450 when incorporated in liposomes [ 175 ]. A randomized, double-blind, placebo-controlled clinical trial in 59 male and female subjects aged 20–69 years found evidence that 16 weeks of diet supplemented with 12 mg/d lutein improved macular pigment density and prevented the loss of resolution due to optical glare [ 176 ], an effect related to blue light absorption by xanthophylls rather than by their antioxidant properties. Recently, xanthophylls have been proposed to operate as light-modulated sunscreen with light absorption, causing trans - cis photoisomerization, promoting their reorientation in the membrane plane and increasing their ability to absorb incident blue light in model membranes as well as in the human retina [ 177 ].…”
Section: Lipids Endowed With Antioxidant Actions In Staple Foodsmentioning
confidence: 99%
“…Carotenoids (L and Z) are thought to pre-filter blue light to reduce the adverse effects of glare disorders, light scattering, and chromatic aberration, thus optimizing contrast sensitivity. Macular pigments act as filters in that they improve vision by increasing both the contrast of objects and their background [33][34][35]. Stringham et al [33] reported that supplementation with a macular carotenoid product increased contrast sensitivity, improving glare incapacity.…”
Section: The Role Of Lutein and Zeaxanthin In Eye Visionmentioning
confidence: 99%